Tropilaelaps mercedesae Infestation Is Correlated with Injury Numbers on the Brood and the Population Size of Honey Bee Apis mellifera - Tial C. Ling; Patcharin Phokasem; Chainarong Sinpoo; Panuwan Chantawannakul; Kitiphong Khongphinitbunjong; Terd Disayathanoowat (Animals, 2023)
Tropilaelaps mercedesae, one of the most devastating parasitic mites of honey bee Apis mellifera hosts, is a major threat to honey products by causing severe damage to honey bee colonies. Here, we recorded injury numbers caused by T. mercedesae to different body parts of the larval, pupal, and crippled adult stages of honey bee A. mellifera. We evaluated the relationship between infestation rate and injury numbers per bee for both larvae and pupae. We also noted the total bee numbers per beehive and examined the relationship between the infestation rate and population size. T. mercedesae infested all developmental stages of honey bees, with the highest injury numbers in the abdomens of bee pupae and the antennas of crippled adult bees. Although larvae received more injury numbers than pupae, both infestation rate and injury numbers decreased as the larval stage progressed to the pupal stage. The infestation rate increased as the population size per beehive decreased. This study provided new perspectives to the understanding of changes in the effects of T. mercedesae infestations on different developmental stages of honey bees. It also showed useful baseline information for screening honey bee stock that might have high defensive behaviors against mite infestation.